2011
DOI: 10.1002/mc.21862
|View full text |Cite
|
Sign up to set email alerts
|

DNA repair genes XPC, XPG polymorphisms: Relation to the risk of colorectal carcinoma and therapeutic outcome with oxaliplatin‐based adjuvant chemotherapy

Abstract: Xeroderma pigmentosum complementation group C and G (XPC, XPG) play important roles in DNA damage repairing machinery. Genetic variations in the XPC and XPG may be associated with increased risk for colorectal carcinoma (CRC). In this study, we evaluated the relation between the XPC Lys939Gln, XPG Asp1104His polymorphisms, and CRC susceptibility in a population-based case-control study, which included 1,028 CRC cases and 1,085 controls. Compared with the corresponding wild genotypes, we found that individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
44
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 43 publications
5
44
1
Order By: Relevance
“…The additional functions of XPG are evident by the presence of structural motifis that are common with proteins involved in repair-recombination and cell cycle regulation (Klungland et al, 1999). It is reported that polymorphisms in XPG are associated with various cancers, such as colorectal cancer, esophageal cancer and lung cancer as well as bladder cancer (Chang et al, 2008;Pan et al, 2009;Rouissi et al, 2011;Liu et al, 2012). However, there was only one study conducted in Chinese population about the association between XPG and gastric cancer risk .…”
Section: Introductionmentioning
confidence: 99%
“…The additional functions of XPG are evident by the presence of structural motifis that are common with proteins involved in repair-recombination and cell cycle regulation (Klungland et al, 1999). It is reported that polymorphisms in XPG are associated with various cancers, such as colorectal cancer, esophageal cancer and lung cancer as well as bladder cancer (Chang et al, 2008;Pan et al, 2009;Rouissi et al, 2011;Liu et al, 2012). However, there was only one study conducted in Chinese population about the association between XPG and gastric cancer risk .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, recent year studies have established that the polymorphisms in DNA repair genes can either change protein coding or alter the levels of transcription or translation, consequently, which can reduce DNA repair capacity and induce genetic instability or carcinogenesis. Few studies have investigated the associations between XPC Lys939Gln and risk of CRC, and these findings were inconsistent (Hansen et al, 2007;Engin et al, 2010;Wu et al, 2011;Liu et al, 2012). Overall, the XPC Lys939Gln was found to be associated with CRC risk in two case-control studies (Wu et al, 2011;Liu et al, 2012) while others did not find any statistically significant associations (Hansen et al, 2007;Engin et al, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…Few studies have investigated the associations between XPC Lys939Gln and risk of CRC, and these findings were inconsistent (Hansen et al, 2007;Engin et al, 2010;Wu et al, 2011;Liu et al, 2012). Overall, the XPC Lys939Gln was found to be associated with CRC risk in two case-control studies (Wu et al, 2011;Liu et al, 2012) while others did not find any statistically significant associations (Hansen et al, 2007;Engin et al, 2010). In this study, although there were no statistically significant association observed between XPC Lys939Gln polymorphism and CRC risk, it is worth to note that current data regarding XPC Lys939Gln polymorphism showed a tendency for a higher risk of developing CRC in heterozygous AC genotypes (P=0.0759) or AC+CC variants carriers (P=0.0903).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations